On some aspects of fock-space multi-reference coupled-cluster singles and doubles energies and optical properties - Manohar, Prashant Uday; Shamasundar, K. R.; Bag, Arijit; Vaval, Nayana; Pal, Sourav (Recent progress in coupled cluster methods: theory and applications, 2010)

Static hyper-polarizability of open shell molecules computed at the FSMRCCSD level using constrained variational approach - Bag, Arijit; Bhattacharya, S.; Pal, S. (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In recent years, there has been a significant development in the analytic derivatives of energy with respect to electric fields based on the state-of-the-art multi-reference coupled-cluster method using Lagrangian based constrained variational approach. So far, the Lagrangian based Fock space multi-reference coupled cluster (FSMRCC) method has been successfully used to calculate electrical dipole moment and polarizability of open shell molecules, particularly, doublet radicals at the ground state and the electronic excited states of closed shell molecules. In this article, Lagrangian based FSMRCC method has been implemented for the first time for calculation of hyper polarizabilites of a few doublet radicals such as OH, OF, NO and NO(2). Orbital-relaxed finite field FSMRCC values are reported for comparison.

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx